“GEVAARLIKE1 TRANSITIONS”: NEGOTIATING HEGEMONIC MASCULINITY AND RITES OF PASSAGE AMONGST COLOURED2 BOYS AWAITING TRIAL ON THE CAPE FLATS. - Cooper, Adam (PINS-Psychology in Society, 2025)
This study looks at the way 25 coloured, Afrikaans speaking boys, awaiting trial for various crimes, position themselves in relation to forms of hegemonic masculinity. Hegemonic masculinity refers to popular ideologies of ideal and actual characteristics of what it means to be a “real man”. These ideologies are located in public spaces and institutions, such as the media, corporate world, military and government. Specifically, the paper explores how forms of hegemonic masculinity influence the boys in this study’s rite of passage into manhood, which is observed in their stories of initiation into gangsterism. Through these tales the boys construct their masculinities in the form of both dominant, global understandings of what it means to be the “real man” and local language and descriptions of practices and rituals. They therefore create hybridised gendered identities, from their particular contexts. Whilst the boys endorse forms of hegemonic masculinity, such as a “Tupac Shakir outlaw” masculinity and a corporate executive masculinity, slivers of ambivalence appear in their discourse. This is due to the fact that these hegemonic masculinities are either largely unattainable or they temporarily empower the boys, but also leave them as children awaiting trial alone.